Investigating the whole picture: Comparing the effects of Airbnb supply and hotel supply on hotel performance across the United States. (August 2020) - Dogru, Tarik; Mody, Makarand; Line, Nathan; Suess, Courtney; Hanks, Lydia; Bonn, Mark
Abstract: This study examines and compares the extent to which Airbnb and hotel supply affect key hotel performance measures in the United States. The results show that although both Airbnb and hotel supply adversely affect hotel revenues (i.e., RevPAR), the magnitude of the impact of hotel supply on RevPAR is much larger than that of Airbnb. Airbnb adversely affects hotel room prices (i.e., ADR), however; it does not affect occupancy rates (i.e., OCC). Yet, increasing hotel supply negatively affects OCC but not ADR. The results from the state-level analyses further showed that the negative effects of Airbnb and hotel supply on RevPAR, ADR and OCC persist only in states with high hotel supply. Analyzing the joint effects of Airbnb and hotel supply on hotel performance in a manner that is both geographically-comprehensive and spatially-meaningful, this study provides a more complete and nuanced understanding on the economic dynamics of the accommodation industry. Highlights: The effect of Airbnb and hotel supply on hotel performance might not be uniform across states. It is unclear the extent to which hotel development have an impact on hotel revenues. The magnitude of the effect of hotel supply on hotel RevPAR is much larger than that of Airbnb. Airbnb supply reduces hoteliers' pricing power while hotel supply reduces individual hotel-level demand.